A terra em Timor-Leste: expondo a injustiça cognitiva nos conflitos fundiários - Maria Paula Meneses (e-cadernos ces)
This article, based on multi-sited fieldwork, examines land tenure conflicts in Timor-Leste, aims to understand the close relationship between the modern property laws and colonial-capitalist strategies of resource appropriation, a relationship that engenders injustices. This socio-legal legacy, present in the existing legal plurality, translates into the co-presence of knowledges and conflict resolution structures, where multiple authorities support the social order based upon a hybrid legality, integrating elements from local justice systems, national and supranational law. In a context in which the State in Timor-Leste constitutionally recognizes and values the norms and the customary, this recognition of the various systems of governance and justice administration present in the country opens up a broader dialogue regarding the socio-legal possibilities of interlegality, an important step towards overcoming cognitive injustices.